Examining the affordable connectivity program and telehealth use: a pilot survey of the affordable connectivity program, telehealth, video and audio visits in a racially diverse, lower-income population - Omolola E. Adepoju; Patrick Dang; Carlos Fuentes; Winston Liaw (Scientific Reports)
Abstract The Affordable Connectivity Program (ACP) aimed to narrow the digital divide by providing discounted internet services for millions of low-income households during the COVID-19 pandemic. This study examined associations between enrollment in the ACP and Telehealth visits in a racially diverse low-income population. Data were obtained via a cross-sectional survey of 213 respondents. Three multivariable regression models examined associations between ACP and three dependent variables, separately: (i) Used telehealth in the past 12 months, (ii) Had 1 or more video visits/consults in the past 12 months, and (iii) Had 1 or more telephone visits/consults in the past 12 months. 41% of survey respondents identified as non-Hispanic Black individuals, 33% as non-Hispanic White individuals, and 22% as Hispanic individuals. 69% reported a pre-tax annual household income of less than $35,000. Only 2 of 10 respondents had heard of ACP and were enrolled, while approximately 4 in 10 had never heard of it. Respondent knowledge/enrollment in the ACP was not significantly associated with telehealth, video consult, or telephone usage. Other demographic characteristics including race, income, educational attainment, and biological sex were significantly associated with telehealth, video, and telephone consults. We observed no association between ACP and telehealth use. While this finding is concerning, it offers an opportunity to reflect on potential reasons for ACP adoption gaps, such as digital literacy, device availability, and potential misconceptions about telehealth services.